A pressure sensor based inductive transducer designed for biomedical applications - Arshad, Atika; Abdul Kadir, Kushsairy; Khan, Sheroz; Alam, A. H. M. Zahirul; Tasnim, Rumana (Institute of Electrical and Electronics Engineers Inc., 2015)
This paper presents an inductive pressure sensor which can be employed for the acquisition of biomedical signal, and these signals can be extremely vital in monitoring and diagnosing human body conditions. Based on the nature of the application, such implementations require precise and real time measurement for measuring any biomedical parameters. The proposed inductive pressure sensor is based on the basic principle of producing inductive changes in response to the movement of a core towards a coil. Using the inductive coil, the physical parameter that is the movement of iron core is translated into a signal with proportionate output frequency change. This type of sensor offers some important criteria like high level of linearity and sensitivity. The proposed pressure sensor can be very effective as it can be used in many biomedical applications.